Effects of lower-limb joint mobility and core muscle activation on dynamic lumbar kyphosis during deep squats - Jaewoo Lee; Youngtae Lim; Moonseok Kwon (Journal of Men's Health, 2025)
Background: Deep squats improves core stability and lower-limb strength. However, dynamic lumbar kyphosis during this movement may increase spinal injury risk. We quantified the dynamic lumbar kyphosis angle during deep squats and examined its association with lower-limb joint angles and muscle activation in the rectus abdominis, external oblique, erector spinae, latissimus dorsi, rectus femoris, gluteus maximus and biceps femoris. Our main aim was to identify strategies for mitigating lumbar kyphosis. Methods: Thirty adult men proficient in resistance training participated in the study. Reflective markers were affixed to joints, and surface electromyography (sEMG) electrodes were placed on muscles involved in lumbar flexion and extension. Participants performed deep squats at 70% of their one-repetition maximum, with motion data captured using eight infrared cameras (sampling rate: 250 Hz). Muscle activity was recorded via a wireless sEMG system (sampling rate: 2000 Hz). Peak joint angles and maximum lumbar flexion were analyzed using correlation and stepwise multiple linear regression to identify factors contributing to dynamic lumbar kyphosis (α = 0.05). Results: Significant positive correlations were observed between maximum hip flexion angle (r = 0.590, p = 0.001), erector spinae activity (r = 0.403, p = 0.027), and maximum lumbar flexion angle. Multiple regression analysis identified a model including hip flexion and erector spinae activity (r = 0.682, adj. R2 = 0.426, p < 0.001), with a hip joint peak flexion angle (HJ_PFA) (t = 3.910, β = 0.553, p = 0.001) as the strongest predictor of lumbar flexion angle, followed by erector spinae muscle activity (ES_MA) (t = 2.436, β = 0.345, p = 0.022). Conclusions: Enhancing hip mobility and erector spinae strengthening prevent dynamic lumbar kyphosis during deep squats. Training programs should incorporate hip mobility exercises, stretching and range of motion routines with resistance exercises targeting the erector spinae.